Over-expression of biomarkers of environmental stress in renal epithelial cells resulting from proapoptotic activity of adriamycin: an immunohistochemical assessment - Pedrycz, Agnieszka; Kosiecz, Daniel; Drelich, Grzegorz; Ossowska, Beata (Current Problems of Psychiatry, 2010)
Introduction: In previous studies authors examined renal cells in rats after adriamycin administration and showed over-expression of proapoptotic effector caspase 3 and also histological changes typical for apoptosis.The mechanisms of adriamycin cytotoxic action involve DNA damage, action of free radicals formed in the process of degradation of this antibiotic, and interactions of both mechanisms. The aim of the current study was to investigate the early answer of renal cells on proapoptotic action of adriamycin. Using the same model of renal epithelial cells from rats treated with adriamycin author determined the expression of proteins (HSP70, p-53) which are known as a biomarkers of cellular stress, using the immunohisto-chemical three-step method. Results and discussion: The results showed that examined in this experimental study cells in response to DNA damage, increased synthesis of p-53 protein and in response to oxidative stress, started overproduction of heat shock protein 70 as a repairing factor. The areas of immunolocalization of these proteins were quantified using an image analysis program. Overproduction of HSP70 is extremely favorable for cells exposed to stress, however it blocks the repair action of p-53. Conclusion: It is also likely that HSP70 inhibitors administered with adriamycin might result in more effective anti-neoplastic therapy for this drug.